2015
DOI: 10.15388/na.2015.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of a class of HIV-1 infection models with latently infected cells

Abstract: Abstract. In this paper, the global dynamics of a class of HIV-1 infection models with different infection rates and latently infected cells are investigated. We first modify the basic virus infection model and propose two models with bilinear infection rate and saturation infection rate, respectively, which take HIV-1 latency into consideration, and then study a model with a general nonlinear infection rate. By using proper Lyapunov functions and LaSalle's invariance principle, it is proved that in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Most of the mathematical models presented in the literature have focused on modeling the interaction between three main compartments: uninfected CD4 + T cells (s), infected cells (y), and free HIV particles (p). Other models have differentiated between latent and active infected cells by introducing a new variable (w) for the latently infected cells [32][33][34][35][36][37]. In [38], an HIV mathematical model has been presented by considering three types of infected cells: latently infected cells (w), short-lived productively infected cells (y), and long-lived productively infected cells (u) as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Most of the mathematical models presented in the literature have focused on modeling the interaction between three main compartments: uninfected CD4 + T cells (s), infected cells (y), and free HIV particles (p). Other models have differentiated between latent and active infected cells by introducing a new variable (w) for the latently infected cells [32][33][34][35][36][37]. In [38], an HIV mathematical model has been presented by considering three types of infected cells: latently infected cells (w), short-lived productively infected cells (y), and long-lived productively infected cells (u) as follows:…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that if N < N crit , then the uninfected steady state is the only steady state in the nonnegative orthant and this steady state is stable; while if N > N crit , then the uninfected steady state is unstable and the endemically infected steady state can be either stable, or unstable and surrounded by a stable limit cycle. Recently, Wang et al [36] studied the following HIV-1 infection model with the mass-action infection rate and latent cells,…”
Section: K2k1t0mentioning
confidence: 99%
“…where is an overall drug efficacy. Furthermore, the model (1) includes the class of HIV infection models for different rates of infection and latently infected cells as investigated in Wang et al [26] .…”
Section: Introductionmentioning
confidence: 99%